Type I Interferon Induction in Cutaneous DNA Damage Syndromes - Klein, Benjamin; Günther, Claudia (Frontiers in Immunology, 2021)
Type I interferons (IFN) as a part of the innate immune system have an outstanding importance as antiviral defense cytokines that stimulate innate and adaptive immune responses. Upon sensing of pattern recognition particles (PRP) such as nucleic acids, IFN secretion is activated and induces the expression of interferon stimulated genes (ISGs). Uncontrolled constitutive activation of the type I IFN system can lead to autoinflammation and autoimmunity. Interferonopathies are monogenic diseases with persistent upregulation of ISGs, resulting in autoinflammatory and autoimmune phenotypes. They are caused by mutations in genes which are involved in sensing or metabolism of intracellular nucleic acids. Many authors described mechanisms of type I IFN secretion upon DNA damage, including the formation of micronuclei or cytosolic chromatin fragments. Hereditary cutaneous DNA damage syndromes share phenotypic features also seen in autoimmune disorders, hence a potential role of DNA-damage-induced type I IFN secretion seems likely. Here, we want to summarize possible mechanisms of IFN induction in cutaneous DNA damage-syndromes with defects in the DNA double-strand repair and nucleotide excision repair. We review recent publications referring to Ataxia teleangiectasia, Bloom syndrome, Rothmund-Thomson syndrome, Werner syndrome, Huriez-syndrome and Xeroderma pigmentosum. Furthermore, we want to discuss the role of type I IFN in cancer and these syndromes.